Canine Hepatozoonosis. First four cases documented in General Pico - La Pampa province - Argentina (Veterinary Science, 2017)
The hepatozoonosis is a parasiticdisease caused by protozoa of the genus Hepatozoonspp. affecting primarily the dog, as wellas other animal species. The definitive host isthe brown tick, Riphicephalus sanguíneus, thattransmits the disease when ingested by the intermediatehost. Clinical symptoms are nonspecificand similar to those produced by other diseasesmost prevalent in the canine population. It ismore severe in puppies less than 1 year of ageand older dogs. The aim of this publication is toreport the first cases of canine hepatozoonosisregistered in the city of General Pico provinceof La Pampa. The presence of gametocytesof Hepatozoon canis was determined in wholeblood drawn from forearm cephalic vein andcolored smears with staining 15. All cases werefrom municipal canilera and were treated at theSmall Animal Teaching Hospital, Faculty of VeterinaryScience, National University of La Pampaand had a history of being infested with ticks.We can say that Hepatozoon canis is present indogs City General Pico clinically and clinicallyincidence occurs with massive infestation ofticks of the genus Riphicephalus sanguineus. Asimportant conclusion would determine diseaseprevalence for action protocols to control thehepatozoonosis and tick population.
Keywords: Hepatozoon canis; Riphicephalus sanguíneus; hemoparasite; canine